Enhancing Peer Greeting Skills in Early Childhood Children with ASD Through SST - Shafa, Qisthy Fathiya; Susetyo, Budi (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
This study investigates the efficacy of Social Skill Training (SST) in enhancing the social skills of children with autism spectrum disorder (ASD) during kindergarten years. Children with ASD often struggle with social interactions, hindering their integration into preschool environments. Using a quantitative approach with a Single Subject Research (SSR) A-B-A design, this research focused on improving the "peer greeting" skill, specifically through waving. Results indicate significant improvement across study phases, with waving frequency increasing from 3-4 times in baseline-1 to 6-7 times during intervention, and further to 9-10 times in baseline-2. The findings underscore the effectiveness of SST in enhancing social skills among children with ASD, particularly in initiating greetings through waving. This research contributes valuable insights into evidence-based interventions for improving social interactions in children with ASD during their formative years.